PENINGKATAN KOMPETENSI MENYUSUN RPP DAN MELAKSANAKAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DENGAN TEKNIK OBSERVASI KELAS BAGI GURU SD NEGERI I BATURETNO - Suyatmini Suyatmini (Universitas PGRI Yogyakarta, 2020)
AbstractThis study aims to improve the competency of preparing lesson plans and implementing learning through academic supervision with classroom observation techniques for teachers of SD Negeri I Baturetno in the 2018/2019 academic year. This study uses the School Action Research method which was conducted in 2 cycles. The setting of this research is SDN 1 Baturetno. The research subjects were 10 class teachers consisting of grade I to VI teachers at SD Negeri 1 Baturetno. Data collection techniques are non-test, in the form of documents, observations, interviews, and field notes. The results of this study are that there is an increase in teacher competence in preparing the Learning Implementation Plan (RPP) and implementing the learning process after academic supervision with classroom observation techniques for grade I to VI teachers of SD Negeri 1 Baturetno 2018/2019 Academic Year by 80% or as much as 8 teachers namely from 2 teachers (20%) in the pre-cycle, in the first cycle to 5 teachers (50%) and in the second cycle to 10 teachers or 100%. For the average value - experienced a total increase of 18.8 (eighteen point eight), namely from the pre-cycle average value of 71 (less category), in the first cycle to 80 (good category) and in the second cycle to 89.8 (very category well). These results indicate that academic supervision with classroom observation techniques can improve the competency of preparing lesson plans and implementing learning for elementary school teachers I Baturetno.Keywords: Teacher Competence, RPP, Learning, Academic Supervision, Class Observation